YEARS clinical decision rule for diagnosing pulmonary embolism: a prospective diagnostic cohort follow-up study in primary care - Frans H Rutten; Menno V Huisman; Jeanet Blom; Rosanne van Maanen; Frederikus A Klok; Geert-Jan Geersing; Karel Moons; Hannah M la Roi-Teeuw; Melchior Nierman; Tuur Egbers (BMJ Open)
Objectives The Wells rule is often used in primary care to rule out pulmonary embolism (PE), but its efficiency is low as many referred patients do not have PE. In this study, we evaluated in primary care an alternative and potentially more efficient diagnostic strategy—the YEARS algorithm; a simplified three-item version of the Wells rule combined with a pretest probability adjusted D-dimer interpretation.Design In this comprehensive prospective diagnostic validation study, primary care patients suspected of PE were enrolled by their general practitioner. All three YEARS items were collected in addition to D-dimer results, and patients were followed for 3 months to establish the final diagnosis.Setting Primary care in the Netherlands.Participants 753 patients with suspected acute PE were included. Five patients (0.7%) were lost to follow-up.Main outcome measures Failure rate (number of PE cases among patients classified by the algorithm as ‘PE ruled-out’) and efficiency (fraction of patients classified as ‘PE probable/further imaging needed’).Results Prevalence of PE was 5.5% (41/748 patients). In total, 603 patients were classified as ‘PE ruled-out’ by the YEARS algorithm (532 with zero YEARS items and a D-dimer<1000 ng/mL and 71 with≥1 positive YEARS item and a D-dimer<500 ng/mL), resulting in an efficiency of 80.6% (603/748 patients, 95% CI 77.6% to 83.4%). Of these patients, three patients had a diagnosis of non-fatal PE during 3 months follow-up, all three with zero YEARS items and D-dimer between 500 and 1000 ng/mL, resulting in an overall diagnostic failure rate of 0.50% (3/603 patients, 95% CI 0.13% to 1.57%). In the patients categorised as ‘imaging needed’ (n=145), a total of 38 (26.2%) were indeed diagnosed with PE.Conclusions Our study suggests that acute PE can be safely ruled out in 80% of patients by the YEARS algorithm in a primary care setting, while only 20% of patients required referral to hospital care for imaging tests. In those classified as ‘imaging needed’, PE was present in about one in every four patients, demonstrating a high detection proportion.